Perianal leiomyoma - Santos, Bruna Fernandes dos; Boarini, Lucas Rodrigues; Oliveira, Pietro Dadalto; Formiga, Fernanda Belotti; Formiga, Galdino José Sitonio; Costa, Anderson da Costa Lino (Journal of Coloproctology, 2017)
Leiomyomas are smooth muscle tumors and may occur in places where these fibers are present, while the anorectal location is rare. They are commonly incidental imaging findings and in most cases, patients are asymptomatic. The therapeutic recommendation is tumor resection and postoperative follow-up. Case report: a 38-year-old Black woman had, one year ago, a swelling in perianal right region, which showed slow and progressive growth. She denied bowel habit alterations, local pain, hematochezia, or tenesmus. Proctologic examination showed a fibroelastic, regular, mobile, painless nodule measuring 10 cm at its largest diameter in the right perianal region, next to the anal verge. The soft tissue ultrasound image identified a solid, hypoechoic, and discreetly vascularized nodule in the perianal, superficial right gluteal region that did not reach the adjacent muscles. A complete resection of perineal tumor was carried out in the ventral position. Histological and immunohistochemical analyses disclosed a leiomyoma with a positive finding for actin smooth muscle and negative for desmin. She is currently asymptomatic and undergoing outpatient follow-up.
Keywords: Gastrointestinal neoplasia; Gastrointestinal stromal tumors; Leiomyoma; Anal canal